Differential Histone Modification Status of Spermatozoa in Relation to Fertility of Buffalo Bulls. Issue 5 (May 2015) - Verma, Arpana; Rajput, Sandeep; Kumar, Sandeep; De, Sachinandan; Chakravarty, Atish Kumar; Kumar, Rakesh; Datta, Tirtha Kumar
ABSTRACT In this study genome‐wide di‐methylated H3K4 (H3K4me2) and tri‐methylated H3K27 (H3K27me3) modification profiles were analyzed in spermatozoa of buffalo bulls having wide fertility differences. The custom designed 4 × 180 K buffalo (Bubalus bubalis) ChIP‐on‐chip array was fabricated by employing array‐based sequential hybridization using bovine and buffalo genomic DNA for comparative hybridization. The buffalo specific array developed had 177, 440 features assembled from Coding sequences, Promoter and CpG regions comprising 2967 unique genes. A total of 84 genes for H3K4me2 and 80 genes for H3K27me3 were found differentially enriched in mature sperm of high and sub‐fertile buffalo bulls. Gene Ontology analysis of these genes revealed their association with different cellular functions and biological processes. Genes identified as differentially enriched between high and sub‐fertile bulls were found to be involved in the processes of germ cell development, spermatogenesis and embryonic development. This study presents the first genome‐wide H3K4me2 and H3K27me3 profiling of buffalo bull sperm. Results provide a list of specific genes which could be made responsible for differential bull fertility. J. Cell. Biochem. 116: 743–753, 2015. © 2014 Wiley Periodicals, Inc.